Predictors of therapeutic failure in GH and prolactin co-secreting pituitary adenomas - Marta Araujo-Castro; Betina Biagetti; Edelmiro Menéndez; Iría Novoa-Testa; Fernando Cordido; Víctor Rodríguez Berrocal; Eider Pascual-Corrales; Fernando Guerrero-Pérez; Almudena Vicente; Rogelio García-Centeno; Laura González; María Dolores Ollero García; et al. (Endocrine Connections)
Aim: To evaluate which factors are associated with a higher probability of failure to surgical and first-generation somatostatin receptor ligands (fgSRLs) treatment in patients with growth hormone and prolactin co-secreting pituitary adenomas (GH&PRL-PAs). Methods: Acromegaly patients with GH&PRL-PAs included in the ACRO-SPAIN study were enrolled. GH&PRL-PAs were defined as tumors with serum PRL levels above the upper limit of normal and positive immunostaining for GH and PRL, or with PRL levels ≥100 ng/mL when immunostaining data were not available. Results: A total of 126 acromegaly patients with GH&PRL-PAs who underwent transsphenoidal pituitary surgery were included, and 42.1% (n = 53) were biochemically cured at the immediate postoperative evaluation. Knosp grade >2 (odds ratio (OR) 3.48, 95% CI 1.28–9.38), higher serum GH (OR 1.01, 95% CI 1.01–1.08) and IGF-1 (OR 1.60, 95% CI 1.05–2.45) levels were associated with a lower probability of surgical cure. Sixty-eight patients received first-line medical therapy as follows: fgSRLs in monotherapy (n = 22), fgSRL plus cabergoline (n = 37), cabergoline in monotherapy (n = 7) and pegvisomant in monotherapy (n = 2). Among the cases treated with fgSRL in monotherapy, 18.2% (n = 4/22) were resistant. We identified as predictors of fgSRL resistance (in monotherapy and combined with cabergoline) a Knosp grade >2 (OR 8.75, P = 0.003), high GH levels at acromegaly diagnosis (OR 1.02, P = 0.031) and higher postoperative GH levels (OR 1.05, P = 0.006), but no predictors of response to fgSRL in monotherapy were identified. Conclusion: The clinical predictors of surgical failure and of fgSRL resistance in patients with GH&PRL-PAs are similar to those described in acromegaly without PRL, co-secretion. Significance statement: In this article focused on GH&PRL pituitary adenomas, we found that a Knosp grade >2, and higher serum GH and IGF-1 levels were associated with a lower probability of surgical cure in these tumors. Regarding the response to fgSRL in monotherapy, 18% of the patients with GH&PRL pituitary adenomas were classified as resistant. Knosp grade >2 (OR 8.75, P = 0.003), high GH levels at acromegaly diagnosis (OR 1.02, P = 0.031), and higher postoperative GH levels (OR 1.05, P = 0.006) were predictors of non-response to fgSRL (monotherapy or combined with cabergoline), while no predictors of response to fgSRL in monotherapy were identified. Thus, we concluded the clinical predictors of surgical failure and of fgSRL resistance in patients with GH&PRL-PAs are similar to those described in acromegaly without PRL co-secretion.